2015
DOI: 10.5114/aoms.2013.39202
|View full text |Cite
|
Sign up to set email alerts
|

State of the art paper Urinary tract infections in pregnancy: old and new unresolved diagnostic and therapeutic problems

Abstract: Urinary tract infections (UTIs) are common in pregnant women and pose a great therapeutic challenge, since the risk of serious complications in both the mother and her child is high. Pregnancy is a state associated with physiological, structural and functional urinary tract changes which promote ascending infections from the urethra. Unlike the general population, all pregnant women should be screened for bacteriuria with urine culture, and asymptomatic bacteriuria must be treated in every case that is diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
132
1
25

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 223 publications
(161 citation statements)
references
References 89 publications
(138 reference statements)
3
132
1
25
Order By: Relevance
“…There is significant statistical variation (P<0.005) between UTI and age group. This is in agreement with other studies [3,8].…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…There is significant statistical variation (P<0.005) between UTI and age group. This is in agreement with other studies [3,8].…”
Section: Resultssupporting
confidence: 83%
“…Also, in agreement with other studies where female showed higher UTI prevalence than male [37][38][39][40]. However, the incident rate in this study is higher than the incidence rates reported in other studies [3,8,12,[41][42][43][44][45], such a difference could be due to geographic location and different in environmental conditions [3], Other factors associated with increasing incidence rate in developing countries such as lack of proper hygiene, different environmental status, population susceptibility, low socio-economic status, sexual intercourse and pregnancy [3,41].…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations